Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Solution q-2r=4
q+r=37


Sagot :

q-2r=4, therefore: q=4+2r.

Plug the value of q into q+r=37, so you get:

4+2r+r=37

3r=37-4=33

3r=33

Therefore: r=11.

q-2r=4, but r=11, so:

q-2(11)=4

q-22=4

Therefore q=26.

Check if the answer is correct using second equation:

q=4+2r=4+2(11)=4+22=26.

So: q=26 and r=11.


to solve these problems we can solve by substitution or elimination method. Now we use the method of elimination.

The first equation :
q - 2r = 4

second equation :
q + r = 37

now elimination equations 1 and 2
[tex]q - 2r = 4\\\underline{q+~r= 37}~-\\~~-3r = -33\\~~~~~~~r = \frac{-33}{-3}\\~~~~~~~r = 11[/tex]

so the value of r is 11

now find the value of q by inserting r into equation 1
[tex]q - 2r = 4\\q - 2(11)=4\\q - 22=4\\q=4+22\\q=26[/tex]

so the value of q is 26

So the value of :
r = 11
q = 26
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.